The language of fictional television : drama and identity - Bednarek, Monika, 1977- (Continuum, 2010)
In this book, Monika Bednarek addresses the need for a systemic analysis of television discourse and characterization within linguistics and media studies. € She presents both corpus stylistics and 'manual' analysis of linguistic and multimodal features of fictional television. The first part focuses on communicative context, multimodality, genre, audience and scripted television dialogue while the second part focuses on televisual characterization, introducing and illustrating the novel concept of 'expressive character identity.'. Aside from the study of television dialogue, which inform.